Evolving Guidelines for Intracameral Injection. Issue 3 (March 2020) - Liebmann, Jeffrey M.; Barton, Keith; Weinreb, Robert N.; Eichenbaum, David A.; Gupta, Preeya K.; McCabe, Cathleen M.; Wolfe, Jeremy D.; Ahmed, Iqbal; Sheybani, Arsham; Craven, E. Randy
Abstract : Purpose: To review evidence and provide guidelines on intracameral (ICM) injection techniques and monitoring. Materials and Methods: A review of published literature on ICM injection and intravitreal injections formed the basis for roundtable deliberations by an expert panel of ophthalmologists. Results: ICM injection as a way to deliver medications is growing in popularity. However, there is limited published literature and no standard approach to best practices for ICM injections, particularly when not accompanying another surgical procedure. Fortunately, there is long clinical experience with ICM manipulation and a large body of evidence surrounding intravitreal injections that has provided important guidance. The expert panel formulates several concrete guidelines and many suggested techniques to help physicians safely and effectively employ ICM injections. Conclusions: This committee addressed the many considerations surrounding ICM injection of drugs or implants and agree that it is a safe and effective surgical procedure when performed with appropriate training and according to established safe practices.